Palladium‐Catalyzed Migratory Insertion of Isocyanides: An Emerging Platform in Cross‐Coupling Chemistry. Issue 28 (10th June 2013) - Vlaar, Tjøstil; Ruijter, Eelco; Maes, Bert U. W.; Orru, Romano V. A.
Abstract Isocyanides have been important building blocks in organic synthesis since the discovery of the Ugi reaction and related isocyanide‐based multicomponent reactions. In the past decade isocyanides have found a new application as versatile C1 building blocks in palladium catalysis. Palladium‐catalyzed reactions involving isocyanide insertion offer a vast potential for the synthesis of nitrogen‐containing fine chemicals. This Minireview discusses all the achievements in this emerging field.